Soft X-ray emission lines in the X-ray binary Swift J1858.6-0814 observed with XMM-Newton-RGS: Disc atmosphere or wind? - Buisson, D. J. K. (2020)
We find soft X-ray emission lines from the X-ray binary Swift J1858.6–0814 in data from XMM–NewtonReflection Grating Spectrometer (RGS): N VII, O VII, and O VIII, as well as notable residuals short of a detection at Ne IX and other higher ionization transitions. These could be associated with the disc atmosphere, as in accretion disc corona sources, or with a wind, as has been detected in Swift J1858.6–0814 in emission lines at optical wavelengths. Indeed, the N VII line is redshifted, consistent with being the emitting component of a P-Cygni profile. We find that the emitting plasma has an ionization parameter log (ξ) = 1.35 ± 0.2 and a density n > 1.5 × 10¹¹ cm⁻³. From this, we infer that the emitting plasma must be within 1013 cm of the ionizing source, ∼5 × 10⁷ rg for a 1.4 M⊙ neutron star, and from the line width that it is at least 10⁴ rg away [2 × 10⁹(M/1.4 M⊙) cm]. We compare this with known classes of emission-line regions in other X-ray binaries and active galactic nuclei.